Air-water interfacial properties of enzymatically hydrolyzed wheat gluten in the presence of sucrose. (December 2017) - Wouters, Arno G.B.; Fierens, Ellen; Rombouts, Ine; Brijs, Kristof; Blecker, Christophe; Delcour, Jan A.
Abstract: Enzymatically hydrolyzed wheat gluten proteins may be a valuable alternative to animal proteins as foaming agents in food. Studies of the air-water (A-W) interfacial properties of such hydrolysates in aqueous solutions contribute to the understanding of their functionality in food systems. We here studied the A-W interfacial characteristics of wheat gluten hydrolysates (GHs) in the absence and presence of sucrose. Sucrose increased (P < 0.05) the foaming capacity, which is the initial amount of foam formed, of GHs. This is probably related to an increased affinity of GHs for the A-W interface in the presence of sucrose, as could be observed by higher (P < 0.05) rates of diffusion to and adsorption at the A-W interface of the GH constituents in sucrose solution compared to those in water. Furthermore, the surface dilatational moduli of GH protein films at A-W interfaces were in most cases higher (P < 0.05) in a sucrose solution than in water. The latter could only partly be related to differences in foam stability. Surface hydrophobicity and intrinsic tryptophan fluorescence measurements revealed that protein conformational changes in the presence of sucrose might be at the basis of the observed differences. Another possibility is that the hydrophilic sucrose molecules in the bulk cause the more hydrophobic protein molecules to concentrate at the interface, more so than in water. In conclusion, it is crucial to investigate the foaming of plant protein hydrolysates in media more complex than water, as other non-surface-active food ingredients alter their interfacial behavior. Graphical abstract: Highlights: The impact of sucrose on interfacial behavior of gluten hydrolysates was studied. Sucrose increased foaming capacity of gluten hydrolysates. This is related to an increased affinity of the hydrolysates for the interface. Hydrolysates also formed stronger interfacial films in the presence of sucrose. The impact of food constituents on the foaming of proteins must be considered.